Neuronal toll like receptor 9 contributes to complete Freund’s adjuvant-induced inflammatory pain in mice - Chen, Yu; Chen, Hui; Li, Xiao-Chen; Mi, Wen-Li; Chu, Yu-Xia; Wang, Yan-Qing; Mao-Ying, Qi-Liang (Frontiers in Molecular Neuroscience, 2022)
Toll like receptor 9 (TLR9) is a critical sensor for danger-associated molecular patterns (DAMPs) and a crucial marker of non-sterile/sterile inflammation among all TLRs. However, the significance of TLR9 in inflammatory pain remains unclear. Here, we subcutaneously injected Complete Freund’s adjuvant (CFA) into the plantar surface of the hind paw, to established a mouse model of inflammatory pain, and we examined expression and distribution of TLR9 in this model. There was a significant increase of TLR9 mRNA and reduction of mechanical paw withdrawal threshold in mice intraplantar injected with CFA. By contrast, mechanical paw withdrawal threshold significantly increased in mice treated with TLR9 antagonist ODN2088. Furthermore, TLR9 is found predominantly distributed in the neurons by immunofluorescence experiment. Accordingly, neuronal TLR9 downregulation in the spinal cord prevented CFA-induced persistent hyperalgesia. Overall, these findings indicate that neuronal TLR9 in the spinal cord is closely related to CFA-induced inflammatory pain. It provides a potential treatment option for CFA-induced inflammatory pain by applying TLR9 antagonist.